Muscle strength in relation to body composition in the Turkish male national judo team - Melekoglu, T.; Öcal, D.; Baydul, B.; Sönmez, M. (Annals of Ovidius University Constanta-Series Physical Education and Sport/Science, movement and health, 2012)
Objectives: The aim of this study was to examine the strength differences in weight categories. For this purpose we have investigated the relationship between body fats and strength of The Turkish National Male Judo Team. Methods: Thirty-nine members of The Turkish Male National Judo Team [n=39, age 19.34 ± 2.71 yr, body mass 81.63 ± 21.67 kg, height 175.26 ± 8.67 cm] were participated as subjects. For body composition profiles, body mass, standing height, lower extremity length (LE), skinfold thickness (biceps, triceps, subscapular, thigh, suppraspinale), body fat percentage (BF %) and body mass index (BMI) were measured. Body fat percentage was estimated by using Brozek method. The strength values were measured from leg and back. The relationship between variables was determined by the Pearson Coefficient Correlation at the significance level of p<0.05. Results: Statistical significant correlations appeared in the leg and back strength with age, height, weight, lower extremity length, BF %, BMI. A negative correlation was found between training history and skinfold thickness. On the other hand, there was no significant correlation between strength values and training history. Also, no correlation was found between weight and skinfold thickness. Conclusions: As judo is a weight classified sport, the correlation of weight and strength is important. The present study demonstrated that age, height, weight, lower extremity length, BF % and BMI effect leg and back strength. Judo players in higher weight classes present higher BF% and strength.